Antibacterial activities against Staphylococcus aureus and Escherichia coli of extracted Piper betle leaf materials by disc diffusion assay and batch experiments. Issue 40 (16th September 2022) - Ngamsurach, Pimploy; Praipipat, Pornsawai
Abstract : The alternative antibacterial material (PBB) is presented with high efficiency and reusability to apply for the disinfection of wastewater systems. Abstract : The use of contaminated water by bacteria may cause many diseases, and thus clean water is needed. Chlorine is normally used for the disinfection of wastewater treatment; however, it produces unwanted odors. Using extracted Piper betle ( P. betle ) is an interesting choice because it is a good chemical compound for bacterial inhibitions. This study attempted to extract P. betle leaf and synthesize P. betle beads (PBB) to characterize materials and investigate antibacterial efficiencies by disc diffusion assay, batch tests, adsorption isotherms, kinetics, and material reusability. The results demonstrated the successful extraction and synthesis of the materials of P. betle . P. betle powder (PBP) had porous and rough surfaces, whereas PBB had a spherical shape with a coarse surface. The four main chemical elements and functional groups of PBP and PBB were carbon, oxygen, calcium, chlorine, and O–H, C–H, N–H, C–O, respectively. The extraction yield and total phenolic, flavonoid, and tannin contents of P. betle were 11.30%, 201.55 ± 0.31 mg GAE per g, 56.86 ± 0.14 mg RE per g, and 41.76 ± 1.32 mg CE per g, respectively. The six main compounds of eugenol, quercetin, apigenin, kaempferol, ascorbic acid, and hydroxychavicol were detected by HPLC analysis. The results of the disc diffusion assay confirmed antibacterial efficiencies of PBB, and the batch tests examined high antibacterial efficiencies of PBB for 100% on Staphylococcus aureus and Escherichia coli . The adsorption isotherms and kinetics of PBB corresponded to Freundlich model and pseudo-second order kinetic model, and the desorption experiments confirmed the reusability of PBB . Therefore, PBB can be possibly applied for an antibacterial purpose in wastewater treatment systems.